Antioxidant activity and physical properties of pH-sensitive biocomposite using poly(vinyl alcohol) incorporated with green tea extract. (August 2020) - Wen, Hanyu; Hsu, Yu-I.; Asoh, Taka-Aki; Uyama, Hiroshi
Abstract: Our study focused on the preparation and characterization of biocomposite films consisting of poly(vinyl alcohol) (PVA) and green tea extract (GTE) with a small amount of glycerol as a plasticizer. Scanning electron microscopy (SEM) showed that both the surface and cross-section of the GTE-PVA biocomposite films were smooth and uniform. Incorporation of GTE could considerably alter the optical and mechanical properties of the pure PVA film. Notably, the GTE-PVA biocomposite films presented better water vapor and UV–vis light barrier properties and higher mechanical strength than the pure PVA film. The antioxidant ability of the biocomposite films was evaluated by measuring the 2, 2-diphenyl-1-picrylhydrazyl radical scavenging and ferric reducing power in terms of the total phenolic content. The GTE-PVA biocomposite films showed higher antioxidant activity than the pure PVA film, and the antioxidant activity increased with increasing GTE concentration. The color of the GTE-PVA biocomposite films became yellow when the pH was lower than 6 and became dark red when the pH was higher than 6. Moreover, color variations were observed in the GTE-PVA biocomposite films by changing the pH. These results suggest that GTE-PVA composite films may be used as a promising antioxidant and visible pH-sensing food packaging materials. Graphical abstract: Image 1 Highlights: Active food packaging film was developed by GTE biomass compounded with PVA. GTE-PVA films have better water vapor and UV barrier properties than pure PVA. Mechanical properties of GTE-PVA films were improved with the content of GTE increased. GTE-PVA films show antioxidant activity and pH-sensitive color change.